Sublingual immunotherapy: World Allergy Organization position paper 2013 update - Giorgio Walter Canonica; Linda Cox; Ruby Pawankar; Carlos E. Baena‐Cagnani; Michael S. Blaiss; С. Бонини; Jean Bousquet; Moisés A. Calderón; Enrico Compalati; Stephen R. Durham; Roy Gerth van Wijk; Désirée Larenas‐Linnemann; et al. (2014)
We have prepared this document, "Sublingual Immunotherapy: World Allergy Organization Position Paper 2013 Update", according to the evidence-based criteria, revising and updating chapters of the originally published paper, "Sublingual Immunotherapy: World Allergy Organization Position Paper 2009", available at http://www.waojournal.org. Namely, these comprise: "Mechanisms of sublingual immunotherapy;" "Clinical efficacy of sublingual immunotherapy" - reporting all the data of all controlled trials published after 2009; "Safety of sublingual immunotherapy" - with the recently published Grading System for adverse reactions; "Impact of sublingual immunotherapy on the natural history of respiratory allergy" - with the relevant evidences published since 2009; "Efficacy of SLIT in children" - with detailed analysis of all the studies; "Definition of SLIT patient selection" - reporting the criteria for eligibility to sublingual immunotherapy; "The future of immunotherapy in the community care setting"; "Methodology of clinical trials according to the current scientific and regulatory standards"; and "Guideline development: from evidence-based medicine to patients' views" - including the evolution of the methods to make clinical recommendations.Additionally, we have added new chapters to cover a few emerging crucial topics: "Practical aspects of schedules and dosages and counseling for adherence" - which is crucial in clinical practice for all treatments; "Perspectives and new approaches" - including recombinant allergens, adjuvants, modified allergens, and the concept of validity of the single products. Furthermore, "Raising public awareness about sublingual immunotherapy", as a need for our patients, and strategies to increase awareness of allergen immunotherapy (AIT) among patients, the medical community, all healthcare stakeholders, and public opinion, are also reported in detail.